PELATIHAN PERANGKAT PEMBELAJARAN TEMATIK TERPADU BERBASIS MODEL INTERACTIVE-COMPENSATORY UNTUK GURU-GURU SEKOLAH DASAR NEGERI CINGCIN 1 KECAMATAN SOREANG KABUPATEN BANDUNG - Ryan Dwi Puspita; Duhita Savira Wardani (Abdimas Siliwangi, 2021)
Primary school teachers are required to be proficient in compiling learning tools. Based on the results of the observations, it was found that some teachers were not proficient in developing integrated thematic learning tools based on special models to improve students' reading comprehension skills. The purpose of this Community ServiceÂ  (CS) is to improve the ability of teachers to compile integrated thematic learning tools based on the Interactive-Compensatory model and implement them in learning in their respective classes. The method used in the implementation of this CS is descriptive. The steps taken in implementing this CS are as follows: (1) Socialization, (2) initial observation (in the form of open interviews), (3) Implementation, (4) Checking learning tools and simulations (samples) of narsum modeling, (5) ) Implementation of learning with the recommended device (2 meetings), (6) Invoice in the form of documents from students, (7) Final evaluation. The results of this CS found that integrated thematic learning tools based on the Interactive-Compensatory model that was trained for SDN Cingcin 1 teachers were useful for improving the ability of teachers to design a special learning device to develop reading comprehension skills. This is evidenced by the results of the implementation in the field obtained an average percentage of more than 60% increase. Some things that must be considered in the application of this learning tool are the availability of supporting books and parental support